Confidence men : Wall Street, Washington, and the education of a president - Suskind, Ron. (New York : Harper, 2011)
Draws on hundreds of hours of interviews and in-depth research to relate the complete story of the nation's financial meltdown, from the trading floors of lower Manhattan to Washington D.C., and examine how Barack Obama responded to the crisis.
Includes bibliographical references (p. [485]-503) and index.
Adult
Adult
Keywords: Financial crises -- United States -- History -- 21st century; Recessions -- United States -- History -- 21st century; Economic policy -- United States; Financial crises -- United States -- History; Recessions -- United States -- History; United States -- Economic policy -- 2009-